Studies on Socio-Demographic Pattern of Dermatomycoses Patients Attending in Rajshahi Medical College Out Patient Department - Nahar, A; Habib, MA; Asadi, KASMZS; Islam, MN; Alam, MS; Ara, S (TAJ: Journal of Teachers Association, 2010)
A total of 2,194 fungal diseases patients (dermatophytoses and candidiasis) were interviewed about their socio-demographic characteristics attending the Skin and V.D. department of Rajshahi Medical College Hospital. It was found that high prevalence of diseases was in age group 21-30 years (46.63%) and females were the more suffered group (60.12%) than the males (39.88%). Among the different occupations, housewives ranked first (41.34%). Tinea corporis were highest in prevalence (44.67%) as compared to other clinical varieties of diseases. Majority of the patients were heavy sweating group (75.89%) and sweating shows a definite association with fungal diseases (P<0.001). It was observed that patients who use oil were less sufferers (37.33%) and who washed their cloths and bed sheets every day also suffered less (10.71%). DOI: 10.3329/taj.v22i1.5035 TAJ 2009; 22(1): 123-127